Почетокот и крајот на мудроста (Проп. 12,9-14)‎ - Ѓоко Ѓорѓевски (ПБФ „Свети Климент Охридски“ - Скопје, 2020)
The Epilogue of the Book of Ecclesiastes is considered as a redactional addition with purpose of synthesising previously stated observations, in many ways different or contrary to traditional wisdom. In an attempt to give a clearer view of the book by analyzing the epilogue, particular attention is paid to the structure of the text.